Human-Centered Approaches to Energy Justice: Pathways Toward Inclusive and Sustainable Economic Growth - Tobari, Tobari (International Journal of Business, Law, and Education, 2026)
This study analyzes a human-centered approach in realizing energy justice as a path to inclusive and sustainable economic growth. The background of this study departs from the global energy access gap, where more than 733 million people are still not connected to electricity and 2.4 billion depend on traditional biomass, thus causing social, economic, and environmental problems. Through systematic literature review and thematic analysis of 45 relevant studies published between 2020–2025, this study identifies three main dimensions of distributive, procedural, and recognition energy justice that are interrelated and must be integrated in implementation. The results of the study show that strategies such as community empowerment, participatory planning, adaptive governance, and financing innovation have been proven to be able to strengthen energy justice while encouraging local economic growth through energy cost savings, job creation, productive capacity building, social infrastructure development, and the birth of innovation and entrepreneurship. However, there are structural obstacles in the form of biased regulations in the centralized system, limited capacity, and political and economic resistance that hinder the scale of implementation. These findings confirm that human-centered approaches are not only normative, but also strategic to ensure the energy transition contributes to sustainable development goals. This research provides recommendations for policymakers and practitioners to prioritize social inclusion, community empowerment, and adaptive governance in global energy transition strategies.